All Days 2012
DOI: 10.2118/158544-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gas Cap and Aquifer Strength on Optimal Well Location for Thin-Oil Rim Reservoirs

Abstract: Many hydrocarbon reservoirs have an oil bearing zone, sandwiched between gas and water bearing zones. For these reservoirs, considerable studies are conducted to optimize the location of wells in the oil rim so as to maximize oil recovery. Few studies however have investigated the conditions under which wells could be located in either the gas cap or the water leg so as to also maximize oil recovery. This study investigates the effect of gas cap and aquifer sizes on oil recovery from a reservoir with a thin oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These factors did not incorporate major operational and reservoir parameters, and the estimation of oil recovery is based on sensitivity analysis. Oil rim recovery has been documented by few authors such as Iyare and Marcelle-De Silva (2012) by initiating sensitivity analysis on important uncertainties that affect oil rim productivity. The results obtained from these methods are from a randomly selected production scheme and static uncertainties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors did not incorporate major operational and reservoir parameters, and the estimation of oil recovery is based on sensitivity analysis. Oil rim recovery has been documented by few authors such as Iyare and Marcelle-De Silva (2012) by initiating sensitivity analysis on important uncertainties that affect oil rim productivity. The results obtained from these methods are from a randomly selected production scheme and static uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental designs were used by Olamigoke and Peacock (2012) to suggest and validate effective screening models for optimizing oil and gas recovery in oil rim reservoirs. Kabir et al (2002) and Obah et al (2012) both designed an experiment with limited uncertainties to develop a response surface model to estimate oil recovery in oil rim reservoirs. Although their work did not include a Pareto analysis, the higher the number of these parameters, the more effective the Pareto analysis of significant parameters.…”
Section: Introductionmentioning
confidence: 99%
“…They highlighted the impact of force balance changes (coning tendency) by increasing the viscous withdrawal with the use of horizontal wells, coupled with gas re-injection to obtain higher recovery efficiency. Iyare and Marcelle-de Silva (2012) carried out an investigation on well placement using a single-well numerical simulator to study the effect of gas cap and aquifer sizes on the production of a thin oil rim reservoir. Their results indicated that placement of the horizontal well below the water-oil-contact (WOC) is more favorable for a large gas cap reservoir; and the well should be placed above gas-oilcontact (GOC) for a reservoir with a small gas cap and large aquifer.…”
Section: Introductionmentioning
confidence: 99%
“…Note that in most cases the optimal recovery rate falls between the critical rate and the maximum recoverable rate for that well. Optimization in this sense is necessary because the critical rate is usually not economical and producing at very high rates leads to early fluid breakthrough which also leads to high production cost or early abandonment of the well, thereby leaving behind large volumes of oil in the reservoir [13,14]. In view of this, a balance must be created between the cost of production (which is a function of years of production before abandonment), the volume of fluid recovered (which is a function of the production rate), and volume of fluid left in the reservoir as a result of abandonment due to coning [15].…”
Section: Introductionmentioning
confidence: 99%